Separación de hecho y los factores que inciden en la disolución del vínculo matrimonial en el distrito judicial de Puno - Hurtado Valencia, Saúl Manuel (2022)
This research work is basic; descriptive, explanatory and dogmatic, based on a systematic induction. Its purpose is to describe the status of the de facto separation and the reasons that cause the dissolution of the marriage bond in the judicial district of Puno. For this purpose, he used the analytical-synthetic, inductive-deductive method, under a mixed approach (quantitative-qualitative). The population was made up of the rulings of thedifferent family courts of the judicial district of Puno. The observation technique was used, the instrument of which was the documentary observation record. As results, the data revealed that the main reasons for the separation of marriages are physical and moral aggression in 44%, unjustified abandonment in 37%, and very serious injury in 15%. In conclusion, the main cause of the dissolution of marriages is physical and moralaggression. Therefore, the magistrates are recommended to rigorously examine these cases in order to issue coherent and fair rulings.